Factors associated with body image dissatisfaction in a Brazilian university sample during the COVID-19 pandemic - Cunha, Carla de Magalhães; Pereira, Emile Miranda; Souto, Maria Clara Reis; de Sá, Laís Barbosa; da Silva, Helena Benes Matos; de Brito, Edleide; de Santana, Mônica Leila Portela (Frontiers in Education, 2023)
We investigated the prevalence of body image dissatisfaction (BID) and associated factors among professors and undergraduate students from Brazil during the COVID-19 pandemic. Using Stunkard's Figure Rating Scale, BID was analysed in a sample of 2,220 adults. The independent variables were sociodemographic, lifestyle, mental health symptoms, COVID-19-related factors, disordered eating, the experience of weight stigma and weight change concerns. We used a multinomial logistic regression analysis. The overall prevalence of BID was 82.5% (69.0% due to excess weight), with more professors dissatisfied by excess than undergraduate students (78.9% vs 61.2%, p< 0.001). In the adjusted model, be a young adult (PR, 1.201, 95% CI: 1.128; 1.279), married or stable union (PR, 1.088, 95% CI: 1.027; 1.152), report of binge eating episode (PR, 1.120, 95% CI: 1.068; 1.173), concern about weight gain (PR, 1.394, 95% CI: 1.310; 1,483) and experience of excess weight stigma (PR, 1.193, 95% CI: 1.141; 1.248) increased the prevalence of BID due to excess weight. While males (PR, 1.578, 95% CI: 1.328; 1.875), moderate to severe depressive symptoms (PR, 1.217, 95% CI: 1.011; 1.465), the concern of losing weight (PR, 1.494, 95% CI: 1.221; 1.830) and experience of low weight stigma (PR, 2.620, 95% CI: 2.093; 3.280) increased the prevalence of BID due low weight. Different factors associated with BID were observed between students and professors. Considering the complexity of body image is essential to consider different public health interventions and the COVID-19 pandemic's influence on reducing BID among Brazilian adults, especially susceptible groups.